2022
DOI: 10.29303/jppipa.v8i5.1834
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Project-Based Learning on Pre-Service Chemistry Teachers’ Self-Efficacy and Critical Thinking Skills

Abstract: The current research aims to: 1) determine the difference between self-efficacy (SE) and critical thinking skills (CTS) of pre-service chemistry teachers who were taught using the PjBL model; and 2) know how much the implementation of the PjBL model influences their self-efficacy (SE) and critical thinking skills (CTS). This experimental research was conducted through a quasi-experimental nonequivalent pretest-posttest control group design. The Cronbach's alpha coefficient value test for the validation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…It could happen because in problem-solving, there are analytical thinking processes, synthesizing, assessing information, and interpretation processes, all of which can develop critical thinking skills (Khusniati et al, 2017;Suardana et al, 2018). This opinion supports the results of research conducted by Uzunoz & Demirhan (2017) and Wahyudiati & Qurniati (2022) that problem-solving in the learning process can improve critical thinking skills. stated that critical thinking is an essential component of the problem-solving process.…”
Section: Critical Thinking Skillsmentioning
confidence: 77%
“…It could happen because in problem-solving, there are analytical thinking processes, synthesizing, assessing information, and interpretation processes, all of which can develop critical thinking skills (Khusniati et al, 2017;Suardana et al, 2018). This opinion supports the results of research conducted by Uzunoz & Demirhan (2017) and Wahyudiati & Qurniati (2022) that problem-solving in the learning process can improve critical thinking skills. stated that critical thinking is an essential component of the problem-solving process.…”
Section: Critical Thinking Skillsmentioning
confidence: 77%
“…[34]. Multiple studies [29,[92][93][94][95][96] have corroborated the positive correlation between general self-efficacy and critical thinking awareness. Research has also shown general self-efficacy can moderate other influencing factors of critical thinking awareness [97,98].…”
Section: Research Hypothesismentioning
confidence: 84%
“…In particular, a study has established a correlation between self-efficacy and critical thinking, indicating that individuals with greater self-efficacy in their academic abilities also exhibit higher levels of critical thinking awareness [99]. Additionally, another two teaching-related studies provided evidence that the "think-pair-share" model and project-based learning have been proven to influence students' critical thinking skills through their impact on self-efficacy [93,100]. General selfefficacy plays an important role in the learning process.…”
Section: Research Hypothesismentioning
confidence: 99%
“…Students with sufficient critical thinking skills have the potential to be able to study problems systematically, face challenges in an organized manner, formulate innovative questions, and design solutions that are seen as relatively new (Johnson, 2007). Critical thinking skills are needed in everyday life (Tax et al, 2011), because they can encourage appropriate and directed decision-making, provide logical reasons, are able to make correct conclusions, so as to achieve the desired results (Bassham et al, 2011). A critical thinker always questions sources of knowledge information, tests the validity of information, analyzes the reliability of information, in order to be able to provide appropriate explanations for certain situations (Brink et al, 2007;Halpern, 2014;Hong et al, 2015).…”
Section: Introductionmentioning
confidence: 99%